2010
DOI: 10.1007/s10956-010-9251-6
|View full text |Cite
|
Sign up to set email alerts
|

Model Based Inquiry in the High School Physics Classroom: An Exploratory Study of Implementation and Outcomes

Abstract: This study considers whether Model Based Inquiry (MBI) is a suitable mechanism for facilitating science as inquiry to allow students to develop deep understandings of difficult concepts, while also gaining better understandings of science process and the nature of science. This manuscript also considers time devoted to MBI in comparison to more traditional demonstration and lecture (TDL) teaching methods, while also revealing the MBI strategy implemented in the physics classroom. Pre-, post-, and delayed-revis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 17 publications
4
32
0
Order By: Relevance
“…Students need to actively use and consequently improve science process skills during an inquiry-based instruction. Quite a number of studies have also showed that inquirybased teaching methods improve students' science process skills (Campbell, Zharg & Neilson, 2011;Ergül, Şimşekli, Çalış, Özdilek, Gökmençelebi, & Şanlı, 2011;Şimşek & Kabapınar, 2010). In this study, when the students' science process skill scores are checked, gain score of inquiry groups (0.93) is higher than those of expository groups (-1.44).…”
Section: Resultsmentioning
confidence: 55%
“…Students need to actively use and consequently improve science process skills during an inquiry-based instruction. Quite a number of studies have also showed that inquirybased teaching methods improve students' science process skills (Campbell, Zharg & Neilson, 2011;Ergül, Şimşekli, Çalış, Özdilek, Gökmençelebi, & Şanlı, 2011;Şimşek & Kabapınar, 2010). In this study, when the students' science process skill scores are checked, gain score of inquiry groups (0.93) is higher than those of expository groups (-1.44).…”
Section: Resultsmentioning
confidence: 55%
“…Through the process of questioning, students are able to build a deep understanding of a concept (Suchman, 1966;Tobin, 1990; Yahudit and Herscovitz, 1999; Hinrichsen and Jarrett, 1999;Campbell, Zhang and Neilson, 2011), science Indonesian Journal of Educational Review, Vol. 4 (1), July 2017 15 process skills and nature of science (Campbell, Zhang and Neilson, 2011) as they are actively involved in the learning process.…”
Section: Questioning Plays An Important Part In the Teaching And Learmentioning
confidence: 99%
“…Through the process of questioning, students are able to build a deep understanding of a concept (Suchman, 1966;Tobin, 1990; Yahudit and Herscovitz, 1999; Hinrichsen and Jarrett, 1999;Campbell, Zhang and Neilson, 2011), science Indonesian Journal of Educational Review, Vol. 4 (1), July 2017 15 process skills and nature of science (Campbell, Zhang and Neilson, 2011) as they are actively involved in the learning process.Typical classroom scenario showed that students rarely ask question as reported by Dillon (1988);Chin (2002); Blonder, Namlok-Naaman and Hofstein (2008). Not much researches were done on students' questions (van Zee et al, 2001) compared to teacher's questions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, McDermott's research indicates that different instructional strategies have different effects on students' learning (McDermott, 2001). What teachers need to understand is that conceptual learning of physics often uses models, animations and simulations for problem solving approaches -Physics by Inquiry (Afra, Osta, & Zoubeir, 2009;Akerson, Hanson, & Cullen, 2007;Campbell, Danhui, & Neilson, 2011). The advances in computer hardware and software programs have provided new platforms for instigating conceptual change and problem solving which physics teachers should tap into it (Dünser, Walker, Horner, & Bentall, 2012;Ülen & Gerlič, 2012;Wieman, Perkins, & Adams, 2008).…”
Section: Introductionmentioning
confidence: 99%